Interferon γ in acute and subacute encephalitis. Issue 6614 (2nd January 1988) - Lebon, P; Boutin, B; Dulac, O; Ponsot, G; Arthuis, M
Abstract : Intrathecal synthesis of interferon γ was shown in 14 out of 16 samples of cerebrospinal fluid collected in the first days of disease in adults, children, and newborn infants with herpes encephalitis. This synthesis was concomitant with that of interferon α and was switched off when the specific antibodies in the central nervous system increased. No endogenous interferon γ was detected in 11 serum samples or 13 samples of cerebrospinal fluid collected early in the course of the disease from patients with measles encephalitis and rubella encephalitis, or in serum and cerebrospinal fluid samples from seven patients with subacute sclerosing panencephalitis. In serum collected after the 10th day after the onset of neurological symptoms interferon γ was present at low concentrations in only three out of 11 serum specimens from patients with measles encephalitis or rubella encephalitis. Interferon γ was present in patients with acute herpes encephalitis and there was active virus replication, but it was not present in postinfectious encephalitis. Possibly the local production of specific antibodies masks the viral antigens and switches off the induction of interferons.